Effectiveness of Brainball program on physical fitness of primary school pupils in Vietnam. A longitudinal study - Pham, Van Han; Rokita, Andrzej; Cichy, Ireneusz; Wawrzyniak, Sara; Bronikowski, Michał (Frontiers in Public Health, 2023)
The present study aimed to evaluate the effectiveness of the Brainballs on the physical fitness of 2nd-grade students at a primary school in Vietnam during and eight months after the experiment. The study concerned 55 pupils (23 boys and 32 girls) aged seven years. The study design was a pedagogical experiment with a parallel-group technique, including experimental and control groups. The examination was carried out in 2019/2020 in three terms pre- (September 2019), post- (January 2020), and follow-up (September 2020). Physical fitness was tested with the use of the International Physical Fitness Test. The Brainball program, conducted twice a week for 35 minutes, combined physical education (PE) with subject-related content, utilizing 100 balls with painted letters, numbers, and signs. Results show that the fitness level was not increased significantly after 20 weeks of the intervention program, neither in experimental nor control groups. However, it significantly improved eight months later at the follow-up examination. The analysis of covariance indicated that pupils from the experimental group improved significantly on most physical fitness as compared to the control group, specifically on the following tests: 50-meter running (p=0.0044), toe touch (p=0.0137), standing long jump (p=0.0076), 4 x 10 m sprint (p =0.0333), hand strength (p=0.0233). These results have shown long-term positive effects of the use of "Brainball" educational balls in physical education classes on the physical fitness development of students, especially in the qualities of speed, strength, and flexibility.